2010
DOI: 10.1007/s10549-010-1172-9
|View full text |Cite
|
Sign up to set email alerts
|

A combined analysis of genome-wide association studies in breast cancer

Abstract: In an attempt to identify common disease susceptibility alleles for breast cancer, we performed a combined analysis of three genome-wide association studies (GWAS), involving 2,702 women of European ancestry with invasive breast cancer and 5,726 controls. Tests for association were performed for 285,984 SNPs. Evidence for association with SNPs in genes in specific pathways was assessed using a permutation-based approach. We confirmed associations with loci reported by previous GWAS on 1p11.2, 2q35, 3p, 5p12, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Recent many genome wide association studies confirmed that prostate, endometrium, breast, gastric and bladder cancer susceptibility linked with the 8q24 locus (Garcia-Closas and Chanock, 2008;Li et al, 2010;Thomas et al, 2009). While 8q24 itself is non-coding and non-genic region, it encompasses established cancer related regions (128,101,433~128,828,043 bp from telomere); the prostate cancer region 3, breast/prostate cancer region, prostate cancer region 1, bladder cancer region, and MYC (Chu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent many genome wide association studies confirmed that prostate, endometrium, breast, gastric and bladder cancer susceptibility linked with the 8q24 locus (Garcia-Closas and Chanock, 2008;Li et al, 2010;Thomas et al, 2009). While 8q24 itself is non-coding and non-genic region, it encompasses established cancer related regions (128,101,433~128,828,043 bp from telomere); the prostate cancer region 3, breast/prostate cancer region, prostate cancer region 1, bladder cancer region, and MYC (Chu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using genome-wide data, and grouping the genetic variants by biological pathways, Li et al (2011) reported suggestive evidence of an association of breast cancer with genes involved in the circadian rhythm. Thus, conducting analyses at the geneor pathway level may be helpful to examine the overall effect of circadian gene polymorphisms on breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether Geninter is able to detect true and false positive SNP-pairs we generated a simulator based on 1,000 breast cancer samples chosen from a cohort of breast cancer patients and controls genotyped on the HumanHap550 SNP microarrays [16]. We estimated the genotype frequencies using these 1,000 samples and randomly chosen 150 SNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Genotype data were obtained on Finnish breast cancer patients genotyped as described previously [16]. Briefly, the patient set comprised two series of unselected breast cancer patients and additional familial cases diagnosed at the Helsinki University Central Hospital (HUCH).The first patient set was collected in 1997-1998 and 2000 and covers 79% of all consecutive, newly diagnosed cases during the collection periods [17,18].…”
Section: Methodsmentioning
confidence: 99%